Mussolini's early diplomacy - Cassels, Alan, 1929- (Princeton, New Jersey : Princeton University Press, 1970)
In October 1922 Mussolini became the constitutional head of the Italian government; by late 1926 he had imposed a Fascist dictatorship on Italy. Professor Cassels, who argues that Mussolini's policies in the 1930s, the era of the Rome- Berlin axis, were foreshadowed by those of the 1920s, traces the stages by which Mussolini took control of Italy's foreign relations. Within the period 1922-1927, Mussolini, biased against democratic states, moved away from Italy's wartime alliance with Britain and France to a policy in favor of authoritarian force. France became the "moral rival"; and the Anglo-Italian entente, calculated to insure British good will, soon cooled as Mussolini sought to realize an Italian empire in the Mediterranean basin. Italy's career diplomats, who at first had tried to restrain Mussolini's adventurism, by 1927 were totally in the background. Mussolini emerges, therefore, as a more radical and far less conventional Italian statesman than he is usually depicted in other historical studies.--
Frontmatter -- Preface -- Contents -- Abbreviations -- Map -- Introduction: The Reception of Fascism -- PHASE ONE: October 1922 to June 1923 -- 1. The Lausanne Conference -- 2. Reparations -- 3. Italian Irredentism on a Leash -- PHASE TWO: July 1923 to May 1924 -- 4. The League of Nations and Corfu -- 5. The Acquisition of Fiume -- 6. Mussolini and German Nationalism -- 7. Eastern Europe -- 8. Fascism Outside Italy: The United States and France -- 9. The Western Mediterranean, France, and Spain -- 10. Colonial Aspirations -- PHASE THREE: June 1924 to April 1925 -- 11. The Matteotti Affair -- PHASE FOUR: May 1925 to February 1927 -- 12. Grandi and Contarini -- 13. Settlement of War Debts -- 14. Locarno and the Alto Adige -- 15. The Anglo-Italian Colonial Entente -- 16. Decisions in the Balkans -- 17. Revisionism on the Danube -- 18. Mussolini's Quarrel with France -- 19. Ideology and Foreign Policy -- 20. The Napoleonic Year, and Stocktaking -- Bibliographical Note -- Index
Includes index.
Print version record.
JSTOR
Keywords: Italy -- Politics and government -- 1922-1945.; Italy -- Foreign relations -- 1922-1945.; Italie -- Politique et gouvernement -- 1922-1945.; Italie -- Relations extérieures -- 1922-1945.; POLITICAL SCIENCE -- International Relations -- General; POLITICAL SCIENCE -- Government -- International; Diplomatic relations; Politics and government; Italy; 1922-1945